Physiological and Biochemical Responses of Ulva prolifera and Ulva linza to Cadmium Stress. (6th March 2013) - Jiang, He-ping; Gao, Bing-bing; Li, Wen-hui; Zhu, Ming; Zheng, Chun-fang; Zheng, Qing-song; Wang, Chang-hai
Abstract : Responses of Ulva prolifera and Ulva linza to Cd 2+ stress were studied. We found that the relative growth rate (RGR), Fv/Fm, and actual photochemical efficiency of PSII (Yield) of two Ulva species were decreased under Cd 2+ treatments, and these reductions were greater in U. prolifera than in U. linza . U. prolifera accumulated more cadmium than U. linza under Cd 2+ stress. While U. linza showed positive osmotic adjustment ability (OAA) at a wider Cd 2+ range than U. prolifera . U. linza had greater contents of N, P, Na +, K +, and amino acids than U. prolifera . A range of parameters (concentrations of cadmium, Ca 2+, N, P, K +, Cl −, free amino acids (FAAs), proline, organic acids and soluble protein, Fv/Fm, Yield, OAA, and K + /Na + ) could be used to evaluate cadmium resistance in Ulva by correlation analysis. In accordance with the order of the absolute values of correlation coefficient, contents of Cd 2+ and K +, Yield, proline content, Fv/Fm, FAA content, and OAA value of Ulva were more highly related to their adaptation to Cd 2+ than the other eight indices. Thus, U. linza has a better adaptation to Cd 2+ than U. prolifera, which was due mainly to higher nutrient content and stronger OAA and photosynthesis in U. linza .